Pengaruh Motivasi dan Kepuasan Kerja terhadap Produktivitas Kerja Pegawai pada PT Tri Keeson Utama Garut - Acep Abdul Basit (Fakultas Ekonomi Universitas Garut, 2016)
This study was conducted to determine the effect of motivation and job satisfaction on employee productivity at PT. Tri Keeson Utama Garut. The data used is primary data. Data analysis technique used is multiple regression. The tools used for data processing in this research are Statistical Package For Social Science (SPSS) version 20 and Microsoft Excel. This research method using descriptive method and causal associative. By using this type of research will be known a significant relationship between the variables studied so as to produce a conclusion that will clarify the picture of the object under study. This research is intended to test the hypothesis by using statistical calculation. Descriptive method with qualitative approach is used to test more in the influence of motivation and job satisfaction on employee productivity. To obtain data in this study using questionnaires, test methods used research instrument is the test of validity and reliability. Hypothesis testing method in the study using the test level of significance both partially and simultaneously, if the value of significance that appears smaller than the error rate then the main hypothesis is rejected. The result of research partially explain that motivation have significant effect to work productivity of employee, and job satisfaction have an effect on signifikan to work productivity of employee. While simultaneously motivation and job satisfaction have a significant effect on work productivity of employees.